The family in face of the elderly's reality of living alone - Marcelo Geovane Perseguino; Ana Lucia de Moraes Horta; Circéa Amalia Ribeiro
ABSTRACT Objective: to understand the family dynamics in face of the reality of the elderly living alone. Method: study of qualitative approach with theoretical reference of symbolic interactionism that involved interviews with families. Data were analyzed by thematic analysis. Results: six families participated in the study. The discourse analysis originated the following categories: The family respecting their decision making; The family organizing itself to the process of living alone after the age of 80 years; The family experiencing the freedom of living alone. Conclusion: in this study, it was possible to identify the facilitation of the possibility of living alone with preparation and agreements between the family during the family life cycle, leading to the feeling of freedom and quality of life of all members. Nursing, as a science responsible for elaborating care strategies, should work together with families to assist in the planning of care plans based on the individual social reality of the family.